Radiation Dose Determination and Body Mass Index (BMI) Evaluation in Abdomen CT Scan Examination Patients Using the Size-Specific Dose Estimate (SSDE) Method - I Made Gede Mas Prawistya Putra; Gusti Ngurah Sutapa; I Gde Antha Kasmawan; Ida Bagus Made Suryatika; I Gusti Agung Putra Adnyana; I Nengah Simpen (Universitas Hamzanwadi, 2025)
A study has been conducted on determining radiation doses and evaluating body mass index (BMI) in patients undergoing CT-Scan Abdomen examinations using the Size Specific Dose Estimate Method at the Bali Mandara Radiology Installation. One of the factors that influences the radiation dose received by patients is the Body Mass Index (BMI). The Size Specific Dose Estimate (SSDE) method is used to assess radiation doses based on patient size, which is often associated with BMI. This study aims to determine the estimated radiation dose of each patient and evaluate the relationship between BMI and the dose received. This study used a CT-Scan brand SIEMENS SOMATOM PERSPECTIVE (serial number 78068). The population in this study were patients undergoing CT-Scan Abdomen examinations. The sample consisted of several BMI categories, namely thin, normal, overweight, and obese. The analysis was carried out using linear regression to measure the relationship between BMI and SSDE, as well as a one-way t-test to see the difference in the average SSDE value in each BMI category. The results showed that each increase in one BMI category caused an increase in SSDE values ​​of 1,566 mGy. The R² value of 98.56% indicated that the BMI category explained almost all of the variability in SSDE values. However, a one-way t-test statistic showed that there was no significant difference in the average SSDE values ​​in the thin, normal, overweight, and obese categories (F count <F table, so H₀ was accepted). This study showed that patients with higher BMI tended to receive higher radiation doses, but the differences between categories were not statistically significant.